1999
DOI: 10.1073/pnas.96.5.2350
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo evaluation of a Taylor-Couette flow, immobilized heparinase I device for clinical application

Abstract: Efficient and safe heparin anticoagulation has remained a problem for continuous renal replacement therapies and intermittent hemodialysis for patients with acute renal failure. To make heparin therapy safer for the patient with acute renal failure at high risk of bleeding, we have proposed regional heparinization of the circuit via an immobilized heparinase I filter. This study tested a device based on Taylor-Couette f low and simultaneous separation͞ reaction for efficacy and safety of heparin removal in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 13 publications
0
15
1
Order By: Relevance
“…Thus, the use of heparinase I or II for the generation of LMWHs requires extreme caution to ensure retaining intact AT-III sites in LMWH fragments. In fact, the results demonstrated herein show that heparinases I or II may be ideal agents for the neutralization of pharmacological doses of heparin (20)(21)(22).…”
Section: Resultsmentioning
confidence: 92%
“…Thus, the use of heparinase I or II for the generation of LMWHs requires extreme caution to ensure retaining intact AT-III sites in LMWH fragments. In fact, the results demonstrated herein show that heparinases I or II may be ideal agents for the neutralization of pharmacological doses of heparin (20)(21)(22).…”
Section: Resultsmentioning
confidence: 92%
“…Fluid-dynamics research provides excellent theoretical and empirical tools for examining the relationships between laminar-shear flow and cell behavior (Adler, 1981;Konstantopoulos et al, 1998;Chen et al, 2004). Specialized flow chambers, such as the Taylor-Couette apparatus (Bartok and Mason, 1957;Goldsmith and Marlow, 1972;Karp-Boss and Jumars, 1998;Ameer et al, 1999), cone-and-plate viscometer (Highgate and Whorlow, 1970;Solomon and Boger, 1998) and many types of microfabricated devices (Dellimore, 1976;Meng et al, 2005), have enabled studies of flow and particle interactions. Several results have shown that flow dominates behavior and cells are transported like passive particles (Rossman, 1937;Happel and Brenner, 1965;Shimeta et al, 1995;Karp-Boss et al, 2000;Dombrowski et al, 2004).…”
Section: Fluid Motion and Single Cellsmentioning
confidence: 99%
“…Activity Assays. Whole-blood recalcification times were used to indirectly determine the amount of heparin present in the blood, as described (16). In most cases with LMWH, anti-Xa activity was used as a surrogate marker to monitor plasma drug levels.…”
Section: Methodsmentioning
confidence: 99%
“…were directly measured by using a modification of published procedures (16). Initial experiments were predicated on the concept that significant absorption of heparin into the bloodstream required efficient delivery of heparin to the deep lung, where particles or droplets of heparin could effectively cross the alveoliblood barrier.…”
Section: Fig 2 Dosing Studies Of Inhaled Lmwh (A)mentioning
confidence: 99%